Professional Athletes' Return to Play and Performance after Achilles Tendon Ruptures. Issue 2 (21st June 2017) - Miller, Johnathan; Woode, Denzel; Jang, Eugene; Trofa, David; Greisberg, Justin; Vosseller, J Turner
Category: Sports Introduction/Purpose: The majority of Achilles tendon ruptures are sports-related. A significant decrease in return to play, playing time, and performance has been shown in National Basketball Association (NBA) players who sustained a complete Achilles tendon rupture requiring surgical repair. However, no study to date has examined and compared the impact on performance and return to play across multiple professional sports. Methods: Publicly available records yielded a list of NBA, National Football League (NFL), Major League Baseball (MLB), and National Hockey League (NHL) athletes who suffered Achilles tendon ruptures requiring surgical repair from 1989-2013. Demographic information and performance-related statistics were recorded from public sports statistics websites. The primary outcome of this study was the proportion of games played post- vs. pre-injury. Secondary markers of longevity were minutes played for NBA, games started for NFL, and innings played in field for MLB. Inclusion criteria included individuals in the NBA, NFL, MLB, and NHL with professional experience for at least 2 years before and after sustaining a primary Achilles tendon rupture requiring surgical repair. A matched control was selected for all returning players by identifying athletes with similar playing position, number of seasons played, and career performance statistics. The study was powered to detect a 15% difference in games played between ruptures and controls. Results: Of 100 athletes initially screened for the study, 43 met the inclusion criteria. Others were excluded for not completing at least 2 seasons pre- (n=16) or post-injury (n=32), or having a confounding injury (n=9). Athletes on average played 75.4% (p < 0.001) and 81.9% (p=0.002) of the games played the season prior to injury at 1 and 2 years post-injury, respectively. Other markers of longevity were also significantly decreased in athletes at 1 and 2 years post-injury (p < 0.001). Athletes also performed worse, with post-injury performances equivalent to 74.8% of pre-injury performance at 1 year (p=0.001) and 77.7% at 2 years (p < 0.001). Compared to controls, athletes with Achilles injuries played fewer games (p < 0.001) and had decreased longevity (p=0.025), and performance statistics (p < 0.001) at 1 year, but not 2 years after injury. Conclusion: An Achilles rupture is a devastating injury with many athletes unable to return to play. Further, athletes who managed to play for 2 years after injury play significantly fewer games, and experience significant decreases in secondary measures of longevity and performance metrics. Compared to controls, however, only the 1-year post-injury longevity and performance statistics were significantly worse. This implies a bimodal distribution of successful return to play: a significant portion of athletes undergoing repair never return to their prior level of competition, but those that do can often perform at a level commensurate with non-injured controls after 2 years.